Farmers’ buying behaviour of herbicides and preference towards weeding operations in Tamil Nadu - PARASURAMAN, BALAJI; KUMAR, AJAY; S, SURENDER; SINGH, PARMINDER; DEEPA, N; VIDHYAVATHI, A; VELAVAN, C; SHEELA, M SHANTHA (The Indian Journal of Agricultural Sciences, 2022)
Herbicides can be regarded an effective tool for managing weeds, and their effective usage can reduce weed-related production losses up to 13%. Mordor Intelligence Report (2022), indicated that during the forecast period (2020–25), the worldwide herbicide market is expected to grow at a CAGR of 2.1%. The aim of the study was to assess the buying behaviour, market potential and constraints faced by the farmers’ during the purchase of herbicides. Study was carried out in selected districts of Tamil Nadu during 2021 with a sample size 200 farmers. The results of this study concluded that there is a significant association between demographic characteristics of the farmers and their preference in weeding operations at 1% significance. Cyperus (78.74), Trianthema (71.45) and Cynodon (69.61) were the major problematic weeds as reported by many of the sample farmers. Buying behavior of farmers’ preference towards product, dealer characteristics and consultancy were the most important parameters for the buying of herbicides.